The 8051 microcontroller and embedded systems : using Assembly and C / Muhammad Ali Mazidi, Janice Gillispie Mazidi, Rolin D. McKinlay - Mazidi, Muhammad Ali; Mazidi, Janice Gillispie; McKinlay, Rolin D. (Pearson/Prentice Hall, 2006)
"This textbook covers the hardware and software features of the 8051 in a systematic and step-by-step way."--Back cover.